Kepemimpinan Kristen dalam Generasi Muda: Karakteristik serta Strategi untuk Mengembangkan Pemimpin Muda yang Efektif (Jurnal Pendidikan Agama dan Teologi, 2025)
Christian leadership is a calling given to all Christians, and it is especially relevant for youth as the next generation. Young people have great potential within themselves, both to lead themselves and others. Therefore, developing leadership in youth is crucial, and this must be done with the right strategies. The primary focus in this development is to emphasize the characteristics of a Christian leader that youth must possess, so they can grow into leaders who are not only competent but also reflect Christ-like values in their lives. This study aims to analyze the characteristics of leaders that the Christian youth must possess and the appropriate strategies for developing their leadership potential. The method used in this study is qualitative with a literature review, in order to gain a deeper understanding of Christian leadership concepts among youth. As the successors of both the church and society, youth must have leadership qualities that begin with leading themselves. This personal leadership will form a strong foundation for young people to answer God’s calling to lead others. The characteristics of a Christian leader that youth must possess include humility, integrity, love, and responsibility. Facing the complex challenges of today’s world, it is essential for youth to have a strong commitment to Christian values, so they are not easily swayed by worldly influences. The church plays a crucial role in guiding and directing youth to understand God's calling, as well as in developing leadership that aligns with Christ’s teachings. With the right development strategies and support from the church, Christian youth can become good leaders. They will be able to make a positive impact in society and reflect the nature of Christ, becoming role models in their daily lives.